Efektifitas Metode Self-Directed Learning Terhadap Pembelajaran Membaca Berbasis Local Wisdom di Institut Studi Islam Sunan Doe - Sulhairi (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
The purpose of this study is to develop an instructional model to improve the self-study skills of Bangkok University students, studying The impact of this model on English reading comprehension them and abilities independent learning and exploring opinions them towards independent learning. This research focuses on several problems, including: (1) To find out factors reason student not enough think critical in read, (2) To know Self-Directed Learning (SDL) is better as teaching material to improve reading skills, (3) Test Content-Based Instructions (CBI) more Good For teach ability read, and (4) evaluation its effectiveness by expert validation and implementation of the model in the classroom. Besides that, the average score after testing students' independent learning abilities in four learning styles significantly higher than those before the test (p.05). This research suggests that the use of story-based learning media, especially those based on local wisdom, plays a big role in motivating students to explore new learning methods. These findings highlight the importance of pedagogical approaches that foster student independence, critical thinking, and engagement, ultimately leading to improved learning outcomes.